Analisis Yuridis Perhitungan Pesangon bagi Pekerja yang Terkena Pemutusan Hubungan Kerja dengan Alasan Efisiensi - Muhamad Restu; Singgih (Indonesian Journal of Law and Justice, 2026)
Termination of employment (PHK) for efficiency reasons is a crucial issue in employment practices in Indonesia, particularly regarding the fulfillment of workers' rights, particularly severance pay. This study aims to legally analyze the severance pay calculation mechanism for workers laid off due to efficiency, referring to the provisions of Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning Job Creation, and its implementing regulations. The research method used is normative legal research with a statutory and conceptual approach. The data used consists of primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that the calculation of severance pay in cases of layoffs due to efficiency has undergone significant changes following the enactment of the new regulations, particularly regarding the amount of compensation received by workers. Under certain conditions, efficiency accompanied by company closure may result in different severance pay entitlements than efficiency without closure. Furthermore, the existence of derivative regulations, such as Government Regulation Number 35 of 2021, clarifies the scheme for providing severance pay, long-service awards, and compensation for rights. Further analysis shows that although the regulation provides a clear legal framework, its application remains open to multiple interpretations, particularly regarding the definition of efficiency and the justification for layoffs by employers. This has implications for potentially suboptimal legal protection for workers. Therefore, consistent interpretation and strengthening of the role of industrial relations dispute resolution institutions are needed to ensure legal certainty and justice for all parties.